2021
DOI: 10.9756/iajafm/v8i1/iajafm0801
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Banking Stability: The Example of Tunisia

Abstract: This paper try to study the factors of the stability of Tunisian banks from a sample made up of 7 Tunisian banks listed during the period 2005-2014. The important determinants used to explain the stability of the banks are: the z-score and the capitalization ratio. The results revealed, firstly, that the profitability variables such as: return on assets (ROA) has a positive and significant impact on the stability of banks and return on equity (ROE) has a negative and significant effect. Besides, bank-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Table 1 lists the dependent, explanatory and control variables used in the study, as well as their associated computations. The first independent variable in our study is NIM which we found in (Mkadmi et al, 2021;Muizzuddin et al, 2021) past research as calculated by net interest income to total assets as a measure of bank profitability. NIM stands for "interest income minus interest costs divided by interest-bearing assets," and it is a measure of the profitability of the banking industry.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 lists the dependent, explanatory and control variables used in the study, as well as their associated computations. The first independent variable in our study is NIM which we found in (Mkadmi et al, 2021;Muizzuddin et al, 2021) past research as calculated by net interest income to total assets as a measure of bank profitability. NIM stands for "interest income minus interest costs divided by interest-bearing assets," and it is a measure of the profitability of the banking industry.…”
Section: Methodsmentioning
confidence: 99%
“…In our research, return on asset (ROA) is also used as a measure of bank profitability. ROA is estimated here by net income to total assets as suggested by Ali and Puah (2019), Audi et al (2021) and Mkadmi et al (2021). The influence of financial institution profitability on institutional stability was determined using NIM and ROA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations